Taxonomy and Natural History of Strumigenys thaxteri Wheeler and Strumigenys reticeps (Kempf) (Hymenoptera: Formicidae) - Lattke, John E.; Silva, Thiago S. R. Da; Delsinne, Thibaut (Zootaxa, 2018)
We report finding Strumigenys thaxteri Wheeler in the Amazonian foothills of southeastern Ecuador, over 2000 km to the west of previously known records for the species in Trinidad and Guyana. Field observations suggest it is a sit and wait ambush predator that captures insects that alight on the vegetation upon which they position themselves. Once prey is subdued they descend with it to ground level, where they presumably nest. Their massive mandibles, robust claws, dense body cover of long silky hairs, and sting may all contribute to detecting, trapping, and subduing larger sized, flying prey. This type of predation is hitherto unreported for the genus. Strumigenys reticeps (Kempf), an apparently closely related species from southern Brazil, may share the same behavior but its key morphological traits are of a lesser degree of development than in S. thaxteri. Both species are redescribed and their morphological variability is discussed. High resolution images of both species are provided. The more frequent use of vegetation beating for ant-collecting is urged. Strumigenys lojanensis Lattke & Aguirre is synonymized as a junior synonym of S. onorei Baroni Urbani & De Andrade.